Simulation of AC-DC converter for DC motor application using fuzzy logic control - Hassan Suliman, Khaled Abubaker (2013)
The AC to DC variable converter becomes an important drive configuration for DC motor applications across a wide range of powers and speeds. Consequently, this converter requires a controller with a high degree of dynamic response. Generally, Proportional-Integral- Differential (PID) controllers have been applied to the converters because of their simplicity. However, PID controller is unable to adapt and approach the best performance when applied to nonlinear system. This problem is solved by the intelligence of the Fuzzy Logic Controller (FLC). Therefore, in this project, simulation of a single phase AC-DC converter is designed to convert AC voltage to variable DC voltage to drive DC motor application with the FLC. In order to obtain the desired speed of dc motor, the FLC is employed to control the firing angle of the power converter. The controller is designed to stabilize the output voltage of AC-DC converter. To verify the effectiveness of the proposed method, both of the FLC and the PID controllers have designed and compared in term of settling time and overshoot. In this project, MATLAB/SIMULINK power system toolbox is used to simulate the proposed system. The simulation result show that the amplitude of output voltage of the DC-AC converter and motor speed can be controlled. Meanwhile, Fuzzy logic controller uses DC motor speed as feedback enhances the system performance by significantly improving the dynamic performance of the AC-DC converter. The simulation results on the real control system reveal that the proposed FLC is able to overcome the disadvantages of conventional PID controller.